Faktor-Faktor yang Berhubungan Dengan Tingkat kepatuhan pasien PGK dalam menjalani hemodialisis. - Ramadhani, Desvi (Universitas Aufa Royhan, 2022)
Introduction: one of the non-communicable diseases that has become a global health problem, namely chronic kidney disease (CKD) is a slow, progressive and irreversible deterioration of kidney function that causes the kidneys to be unable to get rid of waste products. requires renal replacement therapy/hemodialysis/dialysis. Hemodialysis is one of the therapies to remove toxic substances and excess water from the body. The purpose of this study was to determine the factors related to the compliance of kidney disease patients in undergoing hemodialysis treatment in the hemodialysis unit room of arifin achmad hospital. Methods: This study used a descriptive correlative design with a cross sectional approach. The research sample was 58 respondents using purposive sampling technique. This study uses a questionnaire that has been tested for validity and reliability. The analysis used is univariate analysis and bivariate analysis. Results: the results of univariate analysis showed that most of the respondents were middle-aged adults (41-65 years) (81.0%), male gender (53.4%), the education level of the respondents was greater than high school (39.7%), the duration of hemodialysis most of them are 4 years old (70.7%), the respondent’s motivation is mostly high (58,3%), the respondent’s family support is mostly good (70.7%), access to health services, most respondents are easy (79,3%) and the majority of respondents are obedient (77,6%). The person chi-square test showed factors of knowledge (p=0,000), motivation (p=0,0020), family support (p=0,027) and access to health services (p=0,308). Conclusion: there is a significant relationship between knowledge, motivation, and family support with chronic kidney disease patient compliance in undergoing hemodialysis. Knowledge is the most powerful factor associated with this hemodialysis patient compliance. And there is no significant relationship between access to health services with chronic kidney disease patient compliance in undergoing hemodialysis.